The Effect Of Human Resource Empowerment On Employee Performance With Training As A Moderating Variable In The Personnel And Human Resource Development Agency Binjai City - Irma Lestari Silaban; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2025)
Optimal employee training and development is an important factor in improving employee performance in the government sector. This study aims to determine and analyze the effect of HR development on employee performance mediated by training at the Office of the Human Resources Development and Personnel Agency of Binjai City. This study uses a causal associative quantitative approach. The sample used was the entire employee population of 145 people, with a saturated sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results showed that HR development had a positive and significant effect on employee performance, with a T-statistic value of 2.189> 1.96 and a P-value of 0.031 <0.05, indicating that increasing HR development can improve employee performance. In addition, HR development has a positive and significant effect on training, with a T-statistic value of 40.287> 1.96 and a P-value of 0.000 <0.05, indicating that HR development supports increasing employee training. Training also has a positive and significant effect on employee performance, with a T-statistic value of 3.930 > 1.96 and a P-value of 0.000 < 0.05, indicating that increased training can improve employee performance. In addition, training mediates the effect between HR development and employee performance, indicated by a T-statistic value of 3.884 > 1.96 and a P-value of 0.000 < 0.05. These results provide insight that HR development and training are effective strategies in improving employee performance at the Office of the Human Resources Development and Personnel Agency of Binjai City.